Point of sale : analyzing media retail - Herbert, Daniel, 1974-; Johnson, Derek, 1979- (Rutgers University Press, 2020)
Point of Sale offers the first significant attempt to center media retail as a vital component in the study of popular culture. It brings together fifteen essays by top media scholars with their fingers on the pulse of both the changes that foreground retail in a digital age and the history that has made retail a fundamental part of the culture industries. The book reveals why retail matters as a site of transactional significance to industries as well as a crucial locus of meaning and interactional participation for consumers. In addition to examining how industries connect books, DVDs, video games, lifestyle products, toys, and more to consumers, it also interrogates the changes in media circulation driven by the collision of digital platforms with existing retail institutions. By grappling with the contexts in which we buy media, Point of Sale uncovers the underlying tensions that define the contemporary culture industries